Loss of species and genetic diversity during colonization: Insights from acanthocephalan parasites in northern European seals - Sromek, Ludmila; Ylinen, Eeva; Kunnasranta, Mervi; Maduna, Simo N.; Sinisalo, Tuula; Michell, Craig T.; Kovacs, Kit M.; Lydersen, Christian; Ieshko, Evgeny; Andrievskaya, Elena; Alexeev, Vyacheslav; Leidenberger, Sonja; et al. (Wiley, 2023)
Studies on host–parasite systems that have experienced distributional shifts, range fragmentation, and population declines in the past can provide information regarding how parasite community richness and genetic diversity will change as a result of anthropogenic environmental changes in the future. Here, we studied how sequential postglacial colonization, shifts in habitat, and reduced host population sizes have influenced species richness and genetic diversity of Corynosoma (Acanthocephala: Polymorphidae) parasites in northern European marine, brackish, and freshwater seal populations. We collected Corynosoma population samples from Arctic, Baltic, Ladoga, and Saimaa ringed seal subspecies and Baltic gray seals, and then applied COI barcoding and triple-enzyme restriction-site associated DNA (3RAD) sequencing to delimit species, clarify their distributions and community structures, and elucidate patterns of intraspecific gene flow and genetic diversity. Our results showed that Corynosoma species diversity reflected host colonization histories and population sizes, with four species being present in the Arctic, three in the Baltic Sea, two in Lake Ladoga, and only one in Lake Saimaa. We found statistically significant population-genetic differentiation within all three Corynosoma species that occur in more than one seal (sub)species. Genetic diversity tended to be high in Corynosoma populations originating from Arctic ringed seals and low in the landlocked populations. Our results indicate that acanthocephalan communities in landlocked seal populations are impoverished with respect to both species and intraspecific genetic diversity. Interestingly, the loss of genetic diversity within Corynosoma species seems to have been less drastic than in their seal hosts, possibly due to their large local effective population sizes resulting from high infection intensities and effective intra-host population mixing. Our study highlights the utility of genomic methods in investigations of community composition and genetic diversity of understudied parasites.
Keywords: Acanthocephala; genetic diversity; phylogeography; population bottlenecks; population genomics; seal parasites